EVIDENCE OF TELEPORTED BIOELECTROMAGNETIC ENERGY TRANSFER IN A HUMAN MINIORGAN CAUSING DELAY IN CRYSTALLIZATION - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2020)
The purpose of this manuscript is to introduce an optical microscopy methodology documenting an organ inter-tissue parts bioelectromagnetic energy transfer, namely the human hair follicle transferring energy to a short-isolated cut hair shaft segment vertically placed within ≅ 1 mm distance in front of the hair follicle. The human hair has two main parts, follicle and shaft and classified as a miniorgan having its own cell divisions and metabolism. Both the follicle and shaft has been independently documented to emit and receive electromagnetic energy. This work shows a previously unrecognized property of the hair shaft, which is acting as an aerial receiver and conduit of Bioelectromagnetic Fields (BEMFs) emitted by the follicle. The received BEMF energy is transient and transferred via teleportation to be immediately discharged by the cut isolated shaft segment. The discharged crystallization imprint mimics the hair follicle proper BEMFs delaying advance of crystallization.